THE RELATIONSHIP BETWEEN WEBSITE PERFORMANCE, SATISFACTION, AND REVISIT INTENTION - Adam, Mochammad Riyadh; Jiwasiddi, Angtyasti (Emerging Markets : Business and Management Studies Journal, 2016)
RELATIONSHIP